THE EFECT OF WH QUESTION TOWARD GENERATING IDEA IN WRITING OF RECOUNT TEXT AT ELEVENTH GRADE STUDENTS OF SMK AS-SIDIQI LENEK IN THE SCHOOL YEAR 2017 – 2018 - MASHUR (LPPM Universitas Gunung Rinjani, 2020)
The research Purpose was “to know the effectiveness of WH questions to increase the student’s competence in Writing Recount text at Eleventh Grade students of SMK As-Sidiki Lenek in the school year 2017/2018.In this research the researcher used quantitative approach with one group Pre-test-post-test pre-exprimental design because the researcher wants to know the effectiveness of using WH question in writing recount text. The sample is 25 students from population at eleventh grade students. The data were colected by testing technique. The data colected were then analyzed by using t-test formula with aid SPSS 17.0 Windows to compare the result of data. Based on the result of the statistical computation using t-test, the result shows that there is significant differences between pre-test and post-test score. The result of t-test is 5.963. If the result of t-test is compared to t-table with the degree of freedom 24 as stated hypothesis testing, the t-test 5.963 is higher than the t-table 1.711. Therefore, based on the hypothesis testing, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. It means that WH questions as a technique in teaching writing is effective. The researcher of the study suggests, the teacher to apply WH questions technique in their teaching process to increasing the students ability in writing.Key words: WH Question, Writing AbilityTujuan penetian ini adalah “untuk mengetahui pengaruh WH questions dalam meningkatkan kemampuan siswa dalam munulis teks recount pada siswa kelas sebelas di SMK As-Sidiki Lenek tahun pelajaran tahun pelajaran 2017/2018. Dalam penetian ini menggunakan pendekatan kuantitatif dengan satu grup pre-test-post-test rancangan pre-exprimental karena peneliti ingin mengetahui pengaruh menggunakan WH questions dalam menulis teks recount.sampel dalam penetian ini adalah 25 siswa dari populasi pada siswa kelas sebelas di SMK As-Sidikki Lenek. Data telah dikumpulkan menggunakan tehnik pengujian. Data dikumpulkan dari menganalisis dengan menggunakan rumus t-test dengan bantuan SPSS 17.0 Windows untuk membandingkan hasil dari data. Berdasarkan hasil dari perhitungan statistik menggunakan t-test, hasil menunjukkan bahwa ada perbedaan yang signifikan antara nilai pre-test dan post-test. Hasil dari t-test adalah 5.963. Jika hasil dari t-test dibandingkan dengan t-table dengan derajat kebebasan adalah 24 seperti pengujian hipotesis, t-test 5.963 adalah lebih besar dari t-table 1.711. Oleh karena itu, berdasrkan pengujian hipotesis bahwa Hipotesis Alternatif (Ha) adalah diterima dan Hipotesis nol (Ho) adalah ditolak. Itu artinya bahwa pertanyaan WH sebagai tehnik dalam mengajar menulis adalah berpengaruh. Dalam penelitian ini peneliti menyarankan guru untuk mengaplikasikan tehnik pertanyaan WH dalam proses mengajar mereka untuk meningkatkan kemampuan menululis.Kata kunci : pertanyaan menggunakan kata WH, Kemampuan menulis